Demand for human resources in Business schools related careers offered by the University of Guayaquil - Santillán López, Luis Gerardo; Castro Espinoza, Patricia (Revista Universidad de Guayaquil, 2015)
The problem is observed in the perception of crisis quality of employer before the University of Guayaquil, results of evaluations followed by their area of human resources; furthermore, the long work on the image of the University of Guayaquil has been developing over the past decade, the academic units lack a process to enable them to harmonize business needs, the government and non-governmental sector in the country with the proposal undergraduate delivered. This research is both descriptive - exploratory levels. To define the size of the entire population considered organizational sector in zones 5 and 8 according Senplades. With the desire to apply in parallel in the field of study and in the same part of the course students Market Research, then we took over as the joint study group of 171 organizations that voluntarily agreed to participate in the study. The results suggest improvements in the professional profile that should be scheduled in the syllabus, as values, competition and technology innovation in order to be consistent with business requirements, they will be reflected in the curricula of the schools in the short term and generate in shortterms effect of long-term and sustainable it will affect the pursuit of excellence of the Management Faculty and the University, contributing to land changing the productive matrix and the plan of good living.